Metodologia konstrukcji kursu języka obcego dla potrzeb zawodowych - Gajewska, Elżbieta; Sowa, Magdalena (Neofilolog, 2020)
Some of the solutions employed in the field of teaching languages for special purposes have turned out to be useful also in the field of general didactics, e.g. the task-oriented approach. What is particularly valuable in the legacy of teaching languages for special purposes is its eclectic nature, which gives one the possibility to choose and combine the best-tested methods depending on the individual characteristics of every learner. Such an undogmatic approach and search for the best possible technique, which takes into account individual characteristics of each student, appears to be a particularly valuable and enriching one in the days of certain reluctance towards an overtly rigidly defined concept of communicative approach in foreign language teaching.